PERANCANGAN SISTEM INFORMASI ABSENSI MAHASISWA BERBASIS MOBILE MENGGUNAKAN QR CODE PADA UNIVERSITAS MANGKU WIYATA - Linda Evan Englista; Muhammad Khaidir Fahram; Syaechurodji Syaechurodji (LPPM Unbaja, 2026)
The development of mobile technology has encouraged higher education institutions to adopt more efficient information systems, including student attendance systems. However, many universities still apply manual attendance methods, which may lead to inefficiency, data inaccuracies, and potential manipulation. This study aims to analyze and design a Mobile-Based Student Attendance Information System using Quick Response (QR) Code at Universitas Mangku Wiyata. The research method employed is a software development approach using the prototype model. System design is carried out using Unified Modeling Language (UML), including use case diagrams, activity diagrams, sequence diagrams, and class diagrams, to represent system requirements in a structured manner based on the roles of students, lecturers, and academic administrators. In addition, mobile-based interface mockups are developed to illustrate the system workflow. The result of this study is a structured design of a mobile-based student attendance system that is expected to improve the accuracy, transparency, and efficiency of attendance recording. This research is limited to the system design stage; therefore, further studies are required to implement and test the proposed system.